Hadith #1982 - Sahih al-Bukhari - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري (Sahih al-Bukhari)
that his uncle said: “The Prophet (ﷺ) was asked: If a person feels something during his prayer; should one interrupt his prayer?” The Prophet (ﷺ) said: No! You should not give it up unless you hear a sound or smell something.” Narrated Ibn Abi Hafsa: Az-Zuhri said, “There is no need of repeating ablution unless you detect a smell or hear a sound.”
Grade: Sahih

Hadith #3720 - Sahih al-Bukhari - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري (Sahih al-Bukhari)
That he said to the Prophet (ﷺ) “You have not been of any avail to your uncle (Abu Talib) (though) by Allah, he used to protect you and used to become angry on your behalf.” The Prophet (ﷺ) said, “He is in a shallow fire, and had It not been for me, he would have been in the bottom of the (Hell) Fire.”
Grade: Sahih

Hadith #3724 - Sahih al-Bukhari - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري (Sahih al-Bukhari)
Malik bin Sasaa said that Allah’s Messenger (ﷺ) described to them his Night Journey saying, “While I was lying in Al-Hatim or Al-Hijr, suddenly someone came to me and cut my body open from here to here.” I asked Al-Jarud who was by my side, “What does he mean?” He said, “It means from his throat to his pubic area,” or said, “From the top of the chest.” The Prophet (ﷺ) further said, “He then took out my heart. Then a gold tray of Belief was brought to me and my heart was w
Grade: Sahih

Hadith #3993 - Sahih al-Bukhari - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري (Sahih al-Bukhari)
When it was the day (of the battle) of Al-Harra the people were giving Pledge of allegiance to `Abdullah bin Hanzala. Ibn Zaid said, “For what are the people giving Pledge of allegiance to `Abdullah bin Hanzala?” It was said to him, “For death.” Ibn Zaid said, “I will never give the Pledge of allegiance for that to anybody else after Allah’s Messenger (ﷺ) .” Ibn Zaid was one of those who had witnessed the day of Al-Hudaibiya with the Prophet.
Grade: Sahih